Hierarchical Twinning Induced Texture Weakening in Lean Magnesium Alloys - Basu, Indranil; Al-Samman, Talal (Frontiers in Materials, 2019)
Rolled and annealed Mg-1wt. %Zn-1wt. %Gd-0.6wt. %Zr (ZEK110) alloys were subjected to room temperature in-plane compression along the rolling direction, followed by isochronal annealing treatments for 1 h. Despite a starting orientation favoring c-axis extension, the as-deformed microstructure revealed a hierarchical network of twins with profuse quantities of second and third generation twinning appearing within primary tension and compression twins. Complex twin-twin and twin–particle interactions were accompanied by the activation of both basal and non-basal dislocation slip in the neighborhood. While the population density of twins nucleated was significantly high, twin growth was severely retarded due to the presence of secondary phases. In terms of the overall distribution of grain orientations, the as-deformed texture displayed a rather weak basal component with a large portion of the basal poles aligned towards the longitudinal direction with an angular spread of ± 30°. Recrystallization commenced within twins, at twin-twin intersections at lower annealing temperatures and occurred additionally near secondary phases at higher annealing temperatures, giving rise to diverse orientations of both basal and off-basal character. Subsequent growth led to favorable coarsening of the off-basal orientations resulting in an overall texture weakening. The findings provide critical insights with respect to engineering high-strength, high-ductility lean magnesium alloys, comprising hierarchical microstructures that are not only associated with favorable crystallographic textures but additionally display a multi-scale strengthening behavior.